1996
DOI: 10.1074/jbc.271.14.8452
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of p44 and p42 Mitogen-activated Protein Kinase Activation from Receptor-induced Hypertrophy in Neonatal Rat Ventricular Myocytes

Abstract: In response to hormones and mechanical stretch, neonatal rat ventricular myocytes exhibit a hypertrophic response that is characterized by induction of cardiac-specific genes and increased myocardial cell size. Hypertrophic stimuli also activate mitogen-activated protein kinase (MAPK), an enzyme thought to play a central role in the regulation of cell growth and differentiation. To determine if MAPK activation is sufficient for acquisition of the molecular and morphological features of cardiac hypertrophy we c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
126
3
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 42 publications
16
126
3
1
Order By: Relevance
“…Constitutively active MEK1-induced ANF-Luc activation was not inhibited by 30 µM PD98059 (results not shown), confirming that PD98059 acts specifically on MEK1 and does not affect downstream signalling. In contrast, phenylephrine-induced ANF-Luc activation was not affected by PD98059 ( Figure 3C) or dnMEK1 ( Figure 3D), confirming a previous study [21]. These results indicate that activation of the MEK1-ERK pathway is necessary and sufficient for Ang II-induced activation of the ANF promoter but is dispensable for phenylephrine-induced activation of the ANF promoter.…”
Section: Involvement Of Erk Pathway In Ang Ii-or Phenylephrine-inducesupporting
confidence: 90%
See 1 more Smart Citation
“…Constitutively active MEK1-induced ANF-Luc activation was not inhibited by 30 µM PD98059 (results not shown), confirming that PD98059 acts specifically on MEK1 and does not affect downstream signalling. In contrast, phenylephrine-induced ANF-Luc activation was not affected by PD98059 ( Figure 3C) or dnMEK1 ( Figure 3D), confirming a previous study [21]. These results indicate that activation of the MEK1-ERK pathway is necessary and sufficient for Ang II-induced activation of the ANF promoter but is dispensable for phenylephrine-induced activation of the ANF promoter.…”
Section: Involvement Of Erk Pathway In Ang Ii-or Phenylephrine-inducesupporting
confidence: 90%
“…In cultured cardiac myocytes, ERKs are activated by hypertrophic stimuli such as angiotensin II (Ang II) [10], phenylephrine [11,12], endothelin 1 [12][13][14] and PMA [13], as well as cellular stresses such as mechanical stretching [15,16] or osmotic shock [17,18]. Although the role of ERKs in phenylephrineinduced cardiac hypertrophy has been studied by several investigators with different methods, reported roles of ERKs in cardiac hypertrophy vary substantially [19][20][21][22][23]. Furthermore, recent evidence indicates that agonists for the G q -coupled receptor activate not only ERKs but also other members of the MAP kinase family, namely JNK and p38 [17,[24][25][26][27][28], and that these MAP kinases are also important in cardiac hypertrophy [25,26,[29][30][31][32] (reviewed in [5]).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the functional activity of the various pharmacological antagonists closely paralleled their ability to inhibit MAPK activity in these cultures. By inference, this suggests that MAPK participates in the signaling cascade linking mechanical strain to acquisition of the hypertrophic phenotype, a hypothesis that draws support from the studies of others (31)(32)(33). The activity of the inhibitors did not correlate well with their ability to inhibit JNK/SAPK activity.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, antisense oligonucleotides directed against MAPK have been shown to reduce phenylephrine-dependent increments in ANP mRNA levels and ANP promoter activity while, at the same time, suppressing sarcomerogenesis and increments in cell size that typically accompany hypertrophy induced by this agent (33). However, Post et al (32) recently reported that activation of MAPK does not routinely parallel the development of hypertrophy in the cultured myocyte model, and in their hands, dominant-negative mutants of the MAPK pathway failed to suppress phenylephrine-mediated activation of a transfected ANP promoter.…”
mentioning
confidence: 99%
“…Transfection and Immunostaining-For calcium phosphate transfections, purified cardiac myocytes were exposed to a cDNA-calcium phosphate precipitate 24 h after plating (11). A firefly luciferase cDNA controlled by a Rous sarcoma virus promoter and pcDNA3 backbone vector (Invitrogen) or pcDNA3 containing the MEK1 K97M mutant (12) (a kind gift from Natalie Ahn, University of Colorado, Boulder, CO) were co-transfected.…”
Section: Methodsmentioning
confidence: 99%